Transient Triplet Metallopnictinidenes M–Pn (M = PdII, PtII; Pn = P, As, Sb): Characterization and Dimerization - Neben, Marc C.; Wegerich, Nils; Al Said, Tarek A.; Thompson, Richard R.; Demeshko, Serhiy; Dollberg, Kevin; Tkach, Igor; Van Trieste, Gerard P.; Verplancke, Hendrik; von Hänisch, Carsten; Holthausen, Max C.; Powers, David C.; et al. (Journal of the American Chemical Society, 2025)
Nitrenes (R–N) have been subject to a large body of experimental and theoretical studies. The fundamental reactivity of this important class of transient intermediates has been attributed to their electronic structures, particularly the accessibility of triplet vs singlet states. In contrast, electronic structure trends along the heavier pnictinidene analogues (R–Pn; Pn = P–Bi) are much less systematically explored. We here report the synthesis of a series of metallodipnictenes, M–PnPn–M (M = PdII, PtII; Pn = P, As, Sb, Bi) and the characterization of the transient metallopnictinidene intermediates, M–Pn for Pn = P, As, Sb. Structural, spectroscopic, and computational analysis revealed spin triplet ground states for the metallopnictinidenes with characteristic electronic structure trends along the series. In comparison to the nitrene, the heavier pnictinidenes exhibit lower-lying ground state SOMOs and singlet excited states, thus suggesting increased electrophilic reactivity. Furthermore, the splitting of the triplet magnetic microstates is beyond the phosphinidenes M–P dominated by heavy pnictogen atom induced spin–orbit coupling.